2019
DOI: 10.1039/c8em00532j
|View full text |Cite
|
Sign up to set email alerts
|

Impact of traffic volumes on levels, patterns, and toxicity of polycyclic aromatic hydrocarbons in roadside soils

Abstract: The concentrations of ∑16 PAHs and ∑7 carc PAHs in roadside soils were significantly correlated with traffic volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…Inter-site comparisons are somewhat scarcer for PAHs, and their conclusions are non-concordant as well. Kim et al (2019) evidenced a positive correlation between PAHs concentrations in roadside soil and traffic density, however the values fell within a narrow range (∑ 16 PAHs between 0.3-1.8 mg/kg) compared to other studiescf. the data synthesized by Marusenko et al (2011).…”
Section: Introductioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Inter-site comparisons are somewhat scarcer for PAHs, and their conclusions are non-concordant as well. Kim et al (2019) evidenced a positive correlation between PAHs concentrations in roadside soil and traffic density, however the values fell within a narrow range (∑ 16 PAHs between 0.3-1.8 mg/kg) compared to other studiescf. the data synthesized by Marusenko et al (2011).…”
Section: Introductioncontrasting
confidence: 68%
“…PAH concentrations did not exhibit the same dependence on road traffic as copper and zinc. As a reminder, not all examined studies mentioned traffic density as a significant factor influencing PAH contamination either (Kim et al, 2019;Kumar and Kothiyal, 2012;Marusenko et al, 2011). Another remarkable difference with metals was that the contamination levels across all study sites displayed a noticeably lower variability at 0-0.3 m than at 2-3 m (Fig.…”
Section: Case Of Pahsmentioning
confidence: 91%
“…Among the heavier PAHs, benzo[g,h,i]perylene and indeno[1,2,3cd]pyrene show concentrations above the LODs. Generally, these two pollutants are related to diesel vehicular emissions [46][47][48][49][50][51][52] whereas the petrol vehicle emissions are characterized by B[a]P and dibenzo [ah]anthracene emissions [53][54][55][56][57]. For coal combustion, the PAHs profiles are generally characterized by a high presence of fluoranthene, pyrene, phenanthrene and anthracene, to which the chrysene and the isomer of benzo[k]fluorantene are added [58][59][60][61].…”
Section: Organic Fractionmentioning
confidence: 99%
“…Dermal absorption has also been identified as a major exposure pathway, followed by ingestion and inhalation. In Korea, Kim et al (2019) reported a significant CR (5.50E-06) for roadside soil-bound PAHs with the common exposure routes (dermal absorption > ingestion > inhalation) for the CR levels. The soil in Ulsan industrial areas is six times more carcinogenic compare to the soils from roadside traffic-dense areas as reported by Kim et al, 2019.…”
Section: Human Health Risk Levelsmentioning
confidence: 99%
“…Previous studies have focused on the monitoring and distribution of PAHs in agricultural soil, source identification of toxic PAHs, PAH levels in soils in rural, urban, and industrial areas, organic carbon and PAH levels in sediment in coastal areas, and PAH levels in coastal fish. Recently, the CR for roadside soil in traffic-dense regions was investigated (Kim et al, 2019). However, an exhaustive literature review shows that there has been a lack of detailed studies and sensitivity analyses of the CR for sediment-and soil-bound PAHs in coastal and residential areas on the Korean peninsula.…”
Section: Introductionmentioning
confidence: 99%